2014
DOI: 10.3109/15412555.2014.933794
|View full text |Cite
|
Sign up to set email alerts
|

Is Telerehabilitation a Safe and Viable Option for Patients with COPD? A Feasibility Study

Abstract: In patients with COPD non-naïve to rehabilitation we tested the feasibility, adherence and satisfaction of a home-based reinforcement telerehabilitation program (TRP). Outcomes were compared with a standard outpatient rehabilitation program (ORP). Then 18 TRP patients underwent 28 sessions of strength exercises (60 min) and cycle training (40 min) using a satellite platform provided telemonitoring, tele-prescription, video-assistance and phone-calls, patients were equipped with an oximeter, steps-counter, bicy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(137 citation statements)
references
References 35 publications
9
104
0
24
Order By: Relevance
“…The two studies produced an I 2 value of 0%, and the SMD was 0.169 (95% CI: −0.109, 0.448; p =0.23), suggesting no difference between groups (Figure 2). 33,34 The lone PR study by Paneroni and colleagues 32 found statistically significant improvements in both groups (UC: means=397–430.6 m, SD s=57–39.2; p =0.002; TR: means=380–414.2 m, SD s=86–50.8; p =0.008). There was no significant difference between groups ( p =0.91), indicating similar changes.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The two studies produced an I 2 value of 0%, and the SMD was 0.169 (95% CI: −0.109, 0.448; p =0.23), suggesting no difference between groups (Figure 2). 33,34 The lone PR study by Paneroni and colleagues 32 found statistically significant improvements in both groups (UC: means=397–430.6 m, SD s=57–39.2; p =0.002; TR: means=380–414.2 m, SD s=86–50.8; p =0.008). There was no significant difference between groups ( p =0.91), indicating similar changes.…”
Section: Resultsmentioning
confidence: 95%
“…Sparks and colleagues 23 had 93% compliance in the TR group and 83% compliance in the UC group. Paneroni and colleagues 32 reported TR group compliance at 82%, compared with 100% for the UC group, and Varnfield and colleagues 34 had 94% compliance in the TR group and 68% compliance in the UC group. Dalleck and colleagues 31 reported similar compliance rates between groups, with rates at 81% in the TR group and 83% in the UC group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this perspective, programs of telerehabilitation may be more effective compared to telemedicine. Few data are available on this topic, but some trials are going on, showing its safety, feasibility [31] and improvement in dispnoea, quality of life and physical activity [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…58 For those with COPD there is good evidence that pulmonary rehabilitation classes relieve symptoms such as dyspnoea and fatigue, and improve emotional functioning and their uptake should be promoted at every opportunity 59 and, in recent times, pulmonary rehabilitation via telecare has been increasingly advocated as a potential way to deliver such services. 60 With asthma, stress and anxiety can be a trigger for some individuals and there is higher prevalence of psychological problems in those with asthma. 4,61 Those with anxiety and depression tend to have poorer outcomes, so establishing the presence of these comorbidities and discussing management strategies is an important aspect of asthma care.…”
Section: Lifestyle Advice and Triggersmentioning
confidence: 99%